To solve the equation \( x + 11 = -17 \) for \( x \), you should subtract 11 from both sides of the equation. This gives you:
\[ x + 11 - 11 = -17 - 11 \]
Simplifying that leads to:
\[ x = -28 \]
So, the correct response is subtract 11.
to solve the value of x
? (1 point)
Responses
subtract 11
subtract 11
add 11
add 11
add 17
add 17
subtract 17
1 answer
To solve the equation \( x + 11 = -17 \) for \( x \), you should subtract 11 from both sides of the equation. This gives you:
\[ x + 11 - 11 = -17 - 11 \]
Simplifying that leads to:
\[ x = -28 \]
So, the correct response is subtract 11.